Desafios do acesso à justiça pelas mulheres em situação de violência doméstica e/ou familiar: impactos da pandemia da COVID-19 na comarca de Carazinho/RS - Neves, Vivian da Cruz (2022)
The Dissertation aims to understand the impacts of the coronavirus pandemic COVID-19 in cases involving domestic and/or family violence in the District of Carazinho/RS. Given this, the research intended to study how gender relations manifest themselves in society and cause inequality. Starting from the idea of ​​a patriarchal society, he sought to analyze the evolution of women's rights and the challenges they face in accessing justice. From of this, with a new configuration of society resulting from the COVID pandemic 19 sought to verify in the District of Carazinho/RS how the pandemic context contributed to the manifestation of power by domestic violence aggressors and/or family member, in addition to examining the procedures that were adopted in the access to justice for women during social isolation. For studies proposed, the research had as its theoretical framework gender equality and violence domestic and/or family. The approach methods used in the research were the deductive and inductive, seeking for the theoretical content the doctrinal contribution in books and articles in the different disciplines to be covered. As for the method of procedure was a bibliographic and documentary research associated with the collection of statistical data, supported by international instruments and national. The increase in domestic and family violence on a daily basis reflects the how mechanisms are being implemented to combat violence against women, especially if the Maria da Penha Law is effective. If Prior to the COVID-19 pandemic, there were already obstacles in the application of protective standards for women in ituations of domestic and family violence, especially due to the lack of adequate and specialized ectors to provide care humanized; in the pandemic scenario, the difficulties increased greatly, mainly due to the social isolation imposed on the entire Brazilian population and consequently the greater coexistence of women with their aggressors, as well as the closure of public bodies and the absence of electronic means to carry out registrations. Public bodies did not invest in public policies efficient in combating domestic and family violence, so much so that the District of Carazinho/RS was negatively impacted by the COVID-19 pandemic considering that, in the face of social isolation, there was a decrease in records of protective measures and in at least 94 procedures formalized in 2020 no representation hearings were held, and in another 103 hearings were only telephone contacts were made with women to gather their desire for whether or not to proceed with the process, which considerably harmed the right fundamental aspect of access to justice. The negligence in implementing mechanisms to tackling violence against women during the pandemic also promoted Furthermore, gender inequality allows men to exercise power over women women within their own domestic and family environment, strengthening the culture patriarchal.